Evaluation of the impact of chemical control measures and entomological surveillance on Chagas' disease in the counties of Mambaí and Buritinópolis, Goiás State, Brazil - Antonio Carlos Silveira; Rosaura Peñaranda-Carrillo; Elias Seixas Lorosa; João Leite; Márcio Costa Vinhaes; Cleudson Castro; Aluízio Prata; Vanize Macêdo (Sociedade Brasileira de Medicina Tropical (SBMT), 2001)
Epidemiological surveillance activities were implemented in 1980 in Mambaí and Buritinópolis counties, Goiás State. Twenty years later the authors evaluated the impact of these vector control measures on Chagas' disease transmission, based on entomological indicators. Entomological investigation was conducted using the man-hour technique and covering all domiciles. In order to study vector food sources the stomach contents of triatomines were analyzed using the modified precipitins technique. Triatomines were shown to be present in 48 (71.6%) of the 67 locations. Peridomiciliary infestation rates in Mambaí and Buritinópolis were 8.7% and 12.1%, respectively, while intradomiciliary rates were 0.7% and 1.2%. Triatoma sordida was the species identified in 97.3% of all captured specimens. It was also the only species found to be naturally infected with Trypanosoma cruzi. Birds were the most frequent food source (45%) for Triatoma sordida. The most significant result was the complete absence of Triatoma infestans in the two counties.